2019
DOI: 10.18203/2349-3291.ijcp20194156
|View full text |Cite
|
Sign up to set email alerts
|

Calf circumference to detect low birth weight babies: a comparative study

Abstract: Background: In developing countries 15 per cent of infants weigh less than 2,500 grams at birth .It is not possible to provide expensive weighing scales to the community members and families due to logistic (carrying a heavy scale) and operational (inability of Trained Birth Attenders to read) problems. Therefore it is essential to find out an alternative method for the estimation of birth weight. Almost 60 per cent of newborns in developing countries are not weighed. Which can lead to an underestimation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…8,9 The current study showed the mean calf circumference was 7.43±0.389 cm for birth weight group <1800gm which is comparable with the study of Kokku et al, showing mean calf circumference 7.83±0.45cm for birth weight of <2kg. 10 The cut off value of calf circumference for predicting LBW babies by using ROC curve was 7.90cm with maximum sensitivity 97.4% and specificity 84.8%. It has PPV of 73.5% with NPV 98.2% for birth weight <1800gm, followed by length with cut off of 43.75cm and sensitivity (94.9%) and specificity (90.9%) followed by mid-arm circumference with cut off value of 7 [11][12][13] All anthropometric parameters in relation to birth weight were analyzed using ROC curve shows in babies with weight cut off 1800gm, calf circumference showed maximum area under curve (0.989) means it has maximum sensitivity and specificity in identifying weight <1800gm, followed by length (0.979), head circumference (0.963), chest circumference (0.946), mid arm circumference (0.928), thigh circumference (0.821) and foot length (0.735).…”
Section: Discussionmentioning
confidence: 89%
“…8,9 The current study showed the mean calf circumference was 7.43±0.389 cm for birth weight group <1800gm which is comparable with the study of Kokku et al, showing mean calf circumference 7.83±0.45cm for birth weight of <2kg. 10 The cut off value of calf circumference for predicting LBW babies by using ROC curve was 7.90cm with maximum sensitivity 97.4% and specificity 84.8%. It has PPV of 73.5% with NPV 98.2% for birth weight <1800gm, followed by length with cut off of 43.75cm and sensitivity (94.9%) and specificity (90.9%) followed by mid-arm circumference with cut off value of 7 [11][12][13] All anthropometric parameters in relation to birth weight were analyzed using ROC curve shows in babies with weight cut off 1800gm, calf circumference showed maximum area under curve (0.989) means it has maximum sensitivity and specificity in identifying weight <1800gm, followed by length (0.979), head circumference (0.963), chest circumference (0.946), mid arm circumference (0.928), thigh circumference (0.821) and foot length (0.735).…”
Section: Discussionmentioning
confidence: 89%
“…Kokku et al [6] found a positive Pearson's correlation coefficient between CC and LBW, r=0.986 with a mean CC of 9.13 cm. Mani et al [4] found that the mean values of CC were significantly lower in LBW babies (p<0.0001) and the cutoff value in LBW was 9.90 cm with the sensitivity of 85.6% and the specificity of 82.2%.…”
Section: Discussionmentioning
confidence: 97%
“…In pediatrics, this measurement is rarely used as there are no reference data for measuring CC in children. Some studies have demonstrated the possibility of using this measurement as an alternative to weighing at birth, as almost 60% of newborns in developing countries are not weighed 31,32 . In these studies, CC had the highest sensitivity and degree of correlation with birth weight, useful for identifying newborns at risk in communities where scales are unavailable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…31,32 In these studies, CC had the highest sensitivity and degree of correlation with birth weight, useful for identifying newborns at risk in communities where scales are unavailable. The cutoff point for CC in this study was 9.13 cm, 31 and values below this would be considered low birth weight.…”
Section: Arm Measures and Calf Circumferencementioning
confidence: 99%
See 1 more Smart Citation